Pemberian Reward Sebagai Sarana Peningkatan Minat Belajar Anak Di Panti Asuhan Yayasan Mercy Clement Indonesia - Anggi Agustina Sibuea; Fajar Utama Ritonga (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The problems faced by children in orphanages are generally related to learning in the current pandemic season. The limitations of the learning process at school have reduced interest in learning. The target to be achieved at the Mercy Clement Indonesia Foundation Orphanage is to increase children's interest in learning with the reward method. The implementation of this service activity lasts approximately three months from the time of release, and takes place twice a week. The method used in the implementation of this activity is the Group Work method by Zastrow with 5 stages, namely: Intake and contract stages, Member Selection Stage, Assessment and Intervention Planning Stage, Group development stage, and the last stage is the Evaluation and Termination Stage. The results obtained from the implementation of this program can be seen from the increased interest in children's learning at each meeting.